[Rezension von: The architecture of the Scottish medieval church : 1100 - 1560 / Richard Fawcett. - New Haven [Conn.] : Yale Univ. Press, 2011] - Campbell, Ian 1953- (2013)
If ever a book could be described as a ‘magnum opus’ it is this: indeed it is a summa. Richard Fawcett has been publishing on Scottish medieval architecture, mainly ecclesiastical, for three decades, ranging from articles on minute changes in Gothic mouldings (the subject of his doctoral research at the University of East Anglia) such as ‘Dunblane Cathedral: evidence for a change in the design of the nave’ (1982) to a survey of architecture between 370 and 1560, Scottish Architecture from the Accession of the Stewarts to the Reformation (1994). For much of that time he was an Inspector of Ancient Monuments for Historic Scotland, allowing him unfettered access to all the key monuments for most of which he has written authoritative guidebooks. However, besides Scotland, his knowledge of other European medieval architecture, especially in England, France and the Low Countries is encyclopaedic. His researches have made unsustainable the inferiorist attitude that Scottish medieval architecture was insular and backward, by pointing out countless foreign parallels, which demonstrate that Scotland’s patrons and masons were always aware of contemporary developments beyond its borders and shores. This monumental book brings together the fruits of these years of study into a rich synthesis. At last MacGibbon and Ross’ groundbreaking Ecclesiastical architecture of Scotland (1896-7) has been superseded.
Keywords: Scotland, church architecture, Middle Ages, gothic, romanesque architecture, Richard Fawcett; Rezension